Bordetella pertussis FbpA Binds Both Unchelated Iron and Iron Siderophore Complexes - Banerjee, Sambuddha (American Chemical Society, 2014)
[Image: see text] Bordetella pertussis is the causative agent of whooping cough. This pathogenic bacterium can obtain the essential nutrient iron using its native alcaligin siderophore and by utilizing xeno-siderophores such as desferrioxamine B, ferrichrome, and enterobactin. Previous genome-wide expression profiling identified an iron repressible B. pertussis gene encoding a periplasmic protein (FbpA(Bp)). A previously reported crystal structure shows significant similarity between FbpA(Bp) and previously characterized bacterial iron binding proteins, and established its iron-binding ability. Bordetella growth studies determined that FbpA(Bp) was required for utilization of not only unchelated iron, but also utilization of iron bound to both native and xeno-siderophores. In this in vitro solution study, we quantified the binding of unchelated ferric iron to FbpA(Bp) in the presence of various anions and importantly, we demonstrated that FbpA(Bp) binds all the ferric siderophores tested (native and xeno) with μM affinity. In silico modeling augmented solution data. FbpA(Bp) was incapable of iron removal from ferric xeno-siderophores in vitro. However, when FbpA(Bp) was reacted with native ferric-alcaligin, it elicited a pronounced change in the iron coordination environment, which may signify an early step in FbpA(Bp)-mediated iron removal from the native siderophore. To our knowledge, this is the first time the periplasmic component of an iron uptake system has been shown to bind iron directly as Fe(3+) and indirectly as a ferric siderophore complex.